A Research and Development (R&D) roadmap for influenza vaccines: Looking toward the future - Moore, Kristine A.; Ostrowsky, Julia T.; Kraigsley, Alison M.; Mehr, Angela J.; Bresee, Joseph S.; Friede, Martin H.; Gellin, Bruce G.; Golding, Josephine P.; Hart, Peter J.; Moen, Ann; Weller, Charlotte L.; Osterholm, Michael T.; et al. (Vaccine, 2021)
Improved influenza vaccines are urgently needed to reduce the burden of seasonal influenza and to ensure a rapid and effective public-health response to future influenza pandemics. The Influenza Vaccines Research and Development (R&D) Roadmap (IVR) was created, through an extensive international stakeholder engagement process, to promote influenza vaccine R&D. The roadmap covers a 10-year timeframe and is organized into six sections: virology; immunology; vaccinology for seasonal influenza vaccines; vaccinology for universal influenza vaccines; animal and human influenza virus infection models; and policy, finance, and regulation. Each section identifies barriers, gaps, strategic goals, milestones, and additional R&D priorities germane to that area. The roadmap includes 113 specific R&D milestones, 37 of which have been designated high priority by the IVR expert taskforce. This report summarizes the major issues and priority areas of research outlined in the IVR. By identifying the key issues and steps to address them, the roadmap not only encourages research aimed at new solutions, but also provides guidance on the use of innovative tools to drive breakthroughs in influenza vaccine R&D.